AN ANALYSIS OF USING THE GRAPHIC ORGANIZERS ON STUDENTS’ READING COMPREHENSION AT GRADE XI SMA 2 SUNGAI LALA - Athiyah Juliantini; Destri Wahyuningsih (Program Studi Pendidikan Bahasa Inggris, 2026)
Reading comprehension is one of the fundamental skills that students need to master in order to succeed academically. However, many students at Grade XI SMA 2 Sungai Lala face significant difficulties in understanding English reading texts. Graphic organizers are visual tools that have been widely recognized as effective instructional strategies to enhance reading comprehension. This study aimed to analyze the use of graphic organizers on students’ reading comprehension at Grade XI SMA 2 Sungai Lala. This research employed a qualitative method with a descriptive approach. The participants of this study were 30 students of Grade XI and one English teacher. Data were collected through classroom observation, in-depth interviews, and document analysis. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the use of graphic organizers significantly helped students in identifying main ideas, understanding text structure, and making connections between concepts in reading texts. The teacher applied several types of graphic organizers including story maps, Venn diagrams, concept maps, and KWL charts. Students demonstrated improved engagement and comprehension when graphic organizers were employed during the reading process. It was also found that graphic organizers facilitated students in organizing and retaining information more effectively. This study concludes that graphic organizers are beneficial tools in improving students’ reading comprehension and it is recommended that teachers incorporate them consistently into their instructional practices.